2021
DOI: 10.1186/s43055-021-00615-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between epicardial fat volume measured by multi-detector computed tomography and coronary artery disease

Abstract: Background The association between epicardial fat thickness and coronary artery disease (CAD) has been evaluated previously using echocardiography. Recently, multidetector computed tomography (MDCT), as a valuable tool in cardiovascular CT imaging, can improve characterization of CAD and give a more accurate volumetric quantitation of EF. The purpose of our study was to evaluate the relationship between the epicardial fat volume and CAD using multi-detector row CT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…A statistically significance (p<0.001) showed a strong relation with level of Ca score with severity and grading of CAD. A study found that here was significant difference between both groups as regard epicardial fat volume (p < 0.001), and good relation was found between the amount of epicardial fat volume and coronary calcium score, number of affected vessel, plaque burden and degree of stenosis (p < 0.001) (14) . ROC curve of EFV was conducted for prediction of CAD disease activity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A statistically significance (p<0.001) showed a strong relation with level of Ca score with severity and grading of CAD. A study found that here was significant difference between both groups as regard epicardial fat volume (p < 0.001), and good relation was found between the amount of epicardial fat volume and coronary calcium score, number of affected vessel, plaque burden and degree of stenosis (p < 0.001) (14) . ROC curve of EFV was conducted for prediction of CAD disease activity.…”
Section: Discussionmentioning
confidence: 66%
“…Also, a study on 120 patients, 22 patients were negative for CAD, while 98 patients had positive CAD. They found that there was significant difference between negative CTA patients and positive CTA patients as regard epicardial fat volume (p < 0.001) (14) . The mean Calcium score in non-CAD group was 31.28±64.77 and 208.57±89.40 for the CAD group.…”
Section: Discussionmentioning
confidence: 97%
“…Due to its high spatial resolution, dedicated software and post-processing techniques, CCT is the method of choice [19]. In the literature, the attenuation thresholds for post-contrast CCT epicardial fat identification are variable and usually range from −250/−190 HU, as regards the lower limit, to −50/−5 HU for the upper threshold, with intermediate values between the limit values [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EAT volume (EATV) has been recognized as an independent predictor of vulnerable plaques in coronary arteries and is believed to have strong predictive ability (3,7). Multislice spiral computed tomography (CT) has become the preferred method for measuring EATV because of its high spatial resolution, high scanning speed, and reproducibility (8,9). Most studies on the association between EATV and coronary arteriosclerosis have relied on coronary CT angiography (CTA) (10,11).…”
Section: Introductionmentioning
confidence: 99%